Volumetric Changes in Hippocampal Subfields and Memory Performance After Fractionated Brain Radiation Therapy - Hieu Nguyen; Austin B Hopper; Jiwandeep S Kohli; Connor Puett; Anika Christofferson; Roshan Karunamuni; Kathryn R Tringale; Soumya Unnikrishnan; Alena Stasenko; Carrie R McDonald; Jona A Hattangadi-Gluth (Neuro-Oncology, 2026)
Abstract Background The hippocampus comprises discrete anatomic subfields subserving different components of memory. We evaluated longitudinal, dose-dependent volumetric changes in hippocampal subfields after fractionated RT and determined their associations with verbal and visuospatial memory performance. Methods Eighty-nine adults with primary brain tumors received fractionated RT on a prospective clinical trial. High-resolution 3D volumetric MRI and memory tests were obtained at baseline and 3, 6, and 12-months post-RT. Bilateral hippocampi and their thirty-eight subfields were segmented using robust automated parcellation. Linear mixed-effects (LME) models analyzed (1) time-dependent atrophy, (2) dose-volume relationships, and (3) subfield-memory associations at the same timepoint, corrected for multiple comparisons. Results Multiple left and right-sided hippocampal subfields demonstrated significant atrophy at 3, 6, and 12-months post-RT (all p ≤ 0.05). Dose-dependent atrophy was significant at 12 months (p = .01) in the left hippocampus and across all time points in the right (all p ≤ 0.05). Eight right-sided and one left-sided subfield exhibited dose-dependent atrophy across all time points (all p ≤ 0.05). Greater left hippocampal tail and molecular layer volumes were associated with higher verbal memory scores, while greater volumes of multiple right-sided subfields predicted better visuospatial memory performance (all p ≤ 0.05, 𝛽 > 0). Conclusions Fractionated RT induces progressive, dose-related atrophy in discrete hippocampal subfields, with earlier and steeper dose–response curves in right-sided subfields. Higher volumes within multiple left and right-sided subfields were associated with better verbal and visuospatial memory, respectively. Subfield-sparing planning objectives may optimize cognitive outcomes in primary brain tumor patients when hippocampal avoidance is not feasible.